Bacterial Community Composition Associated with Pyrogenic Organic Matter (Biochar) Varies with Pyrolysis Temperature and Colonization Environment - Dai, Zhongmin (mSphere, 2017)
Microbes that colonize pyrogenic organic matter (PyOM) (also called biochar) play an important role in PyOM mineralization and crucially affect soil biogeochemical cycling, while the microbial community composition associated with PyOM particles is poorly understood. We generated two manure-based PyOMs with different characteristics (PyOM pyrolyzed at the low temperature of 300°C [i.e., PyOM300] and at the high temperature of 700°C [i.e., PyOM700]) and added them to high-carbon (4.15%) and low-C (0.37%) soil for microbial colonization. 16S rRNA gene sequencing showed that Actinobacteria, particularly Actinomycetales, was the dominant taxon in PyOM, regardless of the PyOM pyrolysis temperature and soil type. Bacterial communities associated with PyOM particles from high-C soils were similar to those in non-PyOM-amended soils. PyOM300 had higher total microbial activity and more differential bacterial communities than PyOM700. More bacterial operational taxonomic units (OTUs) preferentially thrived on the low-pyrolysis-temperature PyOM, while some specific OTUs thrived on high-pyrolysis-temperature PyOM. In particular, Chloroflexi species tended to be more prevalent in high-pyrolysis-temperature PyOM in low-C soils. In conclusion, the differences in colonized bacterial community composition between the different PyOMs were strongly influenced by the pyrolysis temperatures of PyOM, i.e., under conditions of easily mineralizable C or fused aromatic C, and by other properties, e.g., pH, surface area, and nutrient content. IMPORTANCE Pyrogenic organic matter (PyOM) is widely distributed in soil and fluvial ecosystems and plays an important role in biogeochemical cycling. Many studies have reported changes in soil microbial communities stimulated by PyOM, but very little is known about the microbial communities associated with PyOM. The microbes that colonize PyOMs can participate in the mineralization of PyOM, so changing its structure affects the fate of PyOMs and contributes to soil biogeochemical cycling. This study identified the bacterial community composition associated with PyOMs on the basis of high-throughput sequencing and demonstrated that both PyOM pyrolysis temperature and the colonization environment determined the bacterial community composition. Our work increases our understanding of the dominant phylogenetic taxa associated with PyOMs, demonstrates mechanisms mediating microbial metabolism and growth in PyOMs, and expands a new research area for pyrogenic organic matter. This study identified the bacterial community composition associated with PyOM, which is widely distributed in the environment. Most bacterial OTUs preferentially thrived on PyOM pyrolyzed at low temperature, while some specific OTUs thrived on PyOM pyrolyzed at high temperature.